Stimulasi Perkembangan Psikososial Usia Dewasa Tengah (30-60 Tahun) - Saswati, Nofrida; Harkomah, Isti; Sutinah, Sutinah (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2019)
Most of the people in Legok sub-district are middle-aged adults, some are active as cleaners, fishers, and some are at home taking care of their families. the community does not yet know the psychosocial development of middle adulthood, do not know how to overcome if there are developmental deviations Someone is in the peak of physical readiness to reproduce, including building a household and forming offspring. Transition always means adjusting to new interests, values ​​and behavior patterns. Adults must adjust to various physical changes and must be aware that behavioral patterns at a young age must be radically corrected. Therefore the need for health education is related to stimulation of psychosocial development in middle adulthood. The methods used are lectures and demonstrations. After counseling, there is an increase in community capacity related to how to deal with middle-aged adult deviations